KAJIAN EKOFEMINISME DALAM ESTETIKA SASTRA GOET PAKI ATA KARYA YOSEPH NGADUT - Karolus Budiman Jama (Jurnal Lazuardi, 2021)
Literature is an art that is an element of culture. Literary aesthetics contribute positively in controlling and filling empty spaces in human life. Like literary aesthetics in general, the Manggarai ethnic goet literary aesthetic in Flores has a strategic position in instilling the values ​​of life, be it moral, social, educational, spiritual, and aesthetic values ​​in future generations. This article examines the study of eco-feminism on the literary aesthetics of Yospeh Ngadut's go'et paki ata. This research is classified as a library research using quasi-qualitative research. This research method uses the hermeneutic method to obtain optimal literary meaning of Goet Paki Ata. From the results of data analysis on the literary aesthetic text of Goet Paki ata, the following findings are obtained. The literary aesthetic of Paki Ata's go'et is a philosophical creative process that finds a way back to find another self in nature. The literary aesthetic of Paki Ata's go'et is an aesthetic interpretation that is critical of the dominance of the patriarchal power that subordinates women to seeing nature as herself.